3D flower-like hierarchical NiCo2O4 architecture on carbon cloth fibers as an anode catalyst for high-performance, durable direct urea fuel cells. Issue 45 (6th November 2018) - Ranjani, M.; Senthilkumar, N.; Gnana kumar, G.; Manthiram, Arumugam
Abstract : A 3D NiCo2 O4 hierarchical architecture composed of interlaced and self-stacked 2D nanoflakes is realized as a urea oxidation reaction catalyst for the generation of green energy in direct urea fuel cells. Abstract : Direct urea fuel cells (DUFCs) are considered as promising green energy devices for sustainable energy generation from human waste; however, the lack of efficient urea oxidation reaction electrocatalysts remains a formidable challenge for their practical utility. Herein, we report a flexible, binder-free electrode with a 3-dimensional (3D) hierarchical nickel cobaltite (NiCo2 O4 ) architecture on carbon cloth (CC) fibers for high-performance DUFCs. Benefitting from its unique catalytic nanoarchitecture and direct growth on carbon fibers, NiCo2 O4 /CC-12 demonstrates maximum DUFC power density and durability of 38 mW cm −2 and 180 h, respectively, which significantly outperform DUFC efficiencies reported previously for other catalysts. The influence of dimension, morphology, and chemical structure of the prepared catalysts towards DUFC performance is detailed. Furthermore, considerable improvement in DUFC performance along with enhanced durability is also achieved for NiCo2 O4 /CC-12 with human urine, offering a novel technological platform for the conversion of human waste into sustainable energy.